2010
DOI: 10.1149/1.3425740
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Catalyst Layers for PEMFC Electrodes Prepared by Electrospray Deposition

Abstract: Layers composed of catalyst particles of platinum supported on carbon ͑Pt/C͒ and ionomer phase ͑Nafion͒ have been prepared by electrospray deposition. Some properties are studied, such as morphology; porosity; surface area; thermal decomposition; electroactive area; and single cell testing, relevant to their performance as catalyst layer for proton exchange membrane fuel cell ͑PEMFC͒ electrodes. A dendritic morphology is obtained by electrospray deposition, with enhanced meso-and macroporosity. Thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 38 publications
7
44
0
Order By: Relevance
“…Chaparro et al [25] reported that for an electrospraying process, the optimum Pt loading (cathode) and Nafion content ratio were 0.17 mg/cm 2 and 17 wt%, respectively. The electrospray process homogeneously covered the ionomer film with the Pt/C agglomerate, forming a highly porous material with lower resistivity [26]. Sasikumar et al [29] and Martin et al [21] investigated the optimum Nafion content ratio at various Pt loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Chaparro et al [25] reported that for an electrospraying process, the optimum Pt loading (cathode) and Nafion content ratio were 0.17 mg/cm 2 and 17 wt%, respectively. The electrospray process homogeneously covered the ionomer film with the Pt/C agglomerate, forming a highly porous material with lower resistivity [26]. Sasikumar et al [29] and Martin et al [21] investigated the optimum Nafion content ratio at various Pt loadings.…”
Section: Introductionmentioning
confidence: 99%
“…3 in Ref. ). Figure a displays the distribution obtained with N 2 adsorption, showing the micro and mesopores contributions, below 100 nm pore size, whereas Figure b displays the result from mercury porosimetry, with the meso and macropores contributions, below 100 µm pore size.…”
Section: Resultsmentioning
confidence: 97%
“…(a) Pore size distributions of electrosprayed and airbrushed layers, measured with N 2 adsorption; (b) Pores size distributions from mercury porosimetry (Data taken from ).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of catalyst layers of Pt/C+Nafion by means of electrospray deposition has been described in previous papers (1). Briefly, a suspension of Pt/C (E-TEK, 20 wt%) and Nafion (Aldrich, 5% solution in aliphatic alcohols) is prepared in isopropanol (Panreac).…”
Section: Methodsmentioning
confidence: 99%